THE EFFECTS OF USING VISUAL AIDS IN TEACHING SPEAKING TO THE NINTH CLASS STUDENTS AT SMPN 2 KEREK TUBAN - Ali Fauzi (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2021)
Language is a means of communication used by human beings as a method of communicating ideas, feelings and desires by means of a system of sounds and sounds symbols. It is not only as means of communication but also as media to access knowledge and technology. In Indonesia, English is the first foreign language which has an important role in almost every aspect. It is important not only for students who want to continue their study into the higher education but also for the people who want to look for better job or position. That is why, English is taught from elementary school to the university with the hope that they may prepare their future life. To get this target, the government has applied many methods, techniques, and media to gain successful result. For Junior high school students, instructional media (especially visual Aids) can be interesting things for motivating them to study more diligently because in fact they like them. Students or children like to see and use things as picture, chart, maps or the other visual Aids because they have been familiar with them so that they may be easy to understand, to memorize and to transform things they learn with things they see. Visual Aids can also prevent students from misunderstanding since they can see and even touch what the teacher means. If the students are given chance to see the media used when they are learning English, especially in speaking lesson, so the media will enable to attract them to understand the subject more. At SMPN 2 Kerek Tuban, the researcher tries to prove that teaching English speaking using visual aids is more effective than using only verbal communication. The teachers, especially English teacher has implemented many kinds of methods, techniques and media and he also equips himself with the knowledge of teaching he has taken from Diklat, workshops and seminars. Formerly, he often uses other media when he teaches English speaking. But some of the students feel bored. They are not enthusiastic, not active and even sleepy. That is why, he tries to use media for him it is something new, visual aids. The researcher formulates the problem such as what are the effects of using visual Aids in teaching speaking, how are the visual aids used in teaching speaking, and how are the students’ attitudes toward the use of visual aids. That is why the objective of the research is to describe the effects of visual aids in teaching speaking, to describe how are visual aids used in teaching speaking, and to describe how are students’ attitudes towards the use of visual aids. Based on the researarch, it is seen that visual aids have significant effects in developing English speaking skill for the students. The students are motivated to learn English. The students attitude on the teaching of speaking using visual aids are that they become motivated and interested to learn english so that their speaking skill increase and increase. Therefore, it is sugested that the Englkish teachers have to use visual aids to get the objective of English speaking learning.